Leveraging the psychological well-being among Malaysian engineers: the role of protean career orientation and career strategy implementation - Norizan Baba Rahim (Penerbit Universiti Kebangsaan Malaysia, 2017)
The engineers, deemed to be a protean careerist are notable for their ambitiousness and aggressiveness in pursuing their career advancement and in striving for psychological success. However, the organization’s unaccommodating environment and viewpoint contradicts with this nature of working, which directly and adversely affecting this group’s psychological well-being. Thus, a study on protean career orientation and career strategy implementation and their effects on the psychological well-being of the Malaysian engineers are pertinent and timely. To test the proposed hypotheses, data was collected through self-administered questionnaires. The study sample consisted of 387 engineers from various disciplines regardless of the industries. The hypotheses were analysed using the Partial Least Squares (PLS) approach. This study had found interesting results related to psychological well-being. The findings showed that protean career orientation has a positive influence on career strategy implementation. Finally, this study had found that the relationship between protean career orientation and psychological well-being are not linked through the mediating variable of career strategy implementation. Based on the findings, theoretical and practical implications of the study are discussed. The suggestion for the future research is also offered.